Aplicación del método communicative approach en el desarrollo de la destreza oral del inglés en los estudiantes de cuarto nivel de la escuela de derecho de la universidad nacional de Chimborazo. Propuesta de un manual interactivo para docentes. - Geovanna Elvira, Vallejo Andrade (2016)
This research was developed in order to diagnose the applicability of active methods in the English learning teaching process, for what was designed an interactive manual focused in the teacher’s communicative development process. For that purposed was emphasized the independent variable on the application of the communicative method based on basic and specialized concepts in order to get basic information about the topic, as well the dependent variable 1 based on the development of speaking skills and, also the dependent variable 2 focused on an English manual designed for teachers as proposal. Besides, the methodology was focused in the qualitative, bibliographic and field mode. It was a descriptive research, using a determined population formed by students and teachers of the Law school, taking in account it was not an experimental methodology, emphasized in the scientific and hypothetic deductive method. Throughout the process were used as technique the survey, and as instrument the questionnaire to obtain truthful and objective information of the actors in the investigative process. The theoretical framework includes the Communicative method aligned in the development of student´s oral skills, besides it covers the English teaching process, learning strategies, didactic resources and evaluations.